CLINICAL DATA MANAGEMENT IMPORTANCE IN CLINICAL RESEARCH - Murugesan, Deepa; Banerjee, Ranganath; Ramesh Kumar, Gopal (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Over the last few decades, most of the pharmaceutical companies and research sponsors are facing a lot of challenges in clinical research for their new drug approval. The sponsor research needs a high-quality data report for getting new drug approval from Food and Drug Administration for their medical products. Clinical trial data are important for the drug and medical device development processing pharmaceutical companies to examine and evaluate the efficacy and safety of the new medical product in human volunteers. The results of the clinical trial studies generate the most valuable data and in recent years; there has been massive development in the field of clinical trials. A good clinical data management system reduces the duration of the study and cost of drug development. Further a well-designed case report form (CRF) assists data collection and make facilitates data management and statistical analysis. Nowadays, the electronic data capture (EDC) is very beneficial in data collection. EDC helps to speed up the clinical trial process and reduces the duration, errors and make the work easy in the data management system. This article highlights the importance of data management processes involved in the clinical trial and provides an overview of the clinical trial data management tools. The study concluded that data management tools play a key role in the clinical trial and well-designed CRFs reduces the errors and save the time of the clinical trials and facilitates the drug discovery and development. Keywords: Pharmaceutical, Clinical trial, Clinical data management, Data capture.